2011
DOI: 10.1007/s11684-011-0107-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of stem cell in liver regeneration

Abstract: Liver transplantation is the only life-saving procedure for patients with end-stage liver disease. However, its potential benefits are hampered by many disadvantages, such as the relative shortage of donors, operative risks, and high costs. These issues have prompted the search for new alternative therapies for irreversible liver disease. Stem cell therapy, with the ability for self-renewal and potential for multilineage differentiation, is a promising alternative approach. Several studies have demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…The spleen is the most suitable organ for MSC transplantation for liver regeneration, primarily because these organs have common circulation [11].…”
Section: Resultsmentioning
confidence: 99%
“…The spleen is the most suitable organ for MSC transplantation for liver regeneration, primarily because these organs have common circulation [11].…”
Section: Resultsmentioning
confidence: 99%
“…Two alternative pathways were suggested for the effect of MSCs on liver regeneration: the transdifferentiation of MSCs into hepatocytes and the secretion of growth factors by the administered MSCs, such as vascular endothelial growth factor and HGF. There are many studies showing that MSC administration significantly affects regeneration [25][26][27][28][29][30][31]. However, it is difficult to ignore the studies like that by Popp et al who reported that MSCs did not differentiate into hepatocytes when administered under regenerative conditions; they compared this result with the studies showing that MSCs differentiate into hepatocytes under non-standard conditions or after a long time [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…One principle reason for that is probably the poor quality of human hepatocytes isolated from marginal donor organs not suited for transplantation. Therefore, the search for alternative (stem) cell sources both from hepatic and nonhepatic origin as described above has called for much attention to generate stem cell‐based hepatocytes for the treatment of human liver diseases (47, 130–132). The principles of hepatocyte transplantation are also valid for transplantation of stem cell‐derived hepatocytes.…”
Section: Hepatic Stem Cells and Hepatocyte Transplantationmentioning
confidence: 99%